2019
DOI: 10.1073/pnas.1901794116
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed protein force spectroscopy reveals equilibrium protein folding dynamics and the low-force response of von Willebrand factor

Abstract: Single-molecule force spectroscopy has provided unprecedented insights into protein folding, force regulation, and function. So far, the field has relied primarily on atomic force microscope and optical tweezers assays that, while powerful, are limited in force resolution, throughput, and require feedback for constant force measurements. Here, we present a modular approach based on magnetic tweezers (MT) for highly multiplexed protein force spectroscopy. Our approach uses elastin-like polypeptide linkers for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 86 publications
(147 reference statements)
4
75
0
Order By: Relevance
“…In their study, surface attachment of SA was yet accomplished by one or several of its various amine groups (movie S1), resulting in a less defined attachment geometry and most probably on average weaker mechanical stability. With constant force measurements in magnetic tweezers, Löf et al (23) have shown that the lifetimes of single SA/biotin bonds for SA attached by its various amines are spread over a wide range and, on average, are about 10 times lower than the lifetime of a single bond between biotin and 1SA anchored by the C terminus of its functional subunit. In the present study, we use the latter, mechanically stronger, attachment geometry to investigate the molecular roots of this discern-ible dependence of mechanical stability on force-loading geometry.…”
Section: Different Unbinding Forces For Different Binding Geometriesmentioning
confidence: 99%
“…In their study, surface attachment of SA was yet accomplished by one or several of its various amine groups (movie S1), resulting in a less defined attachment geometry and most probably on average weaker mechanical stability. With constant force measurements in magnetic tweezers, Löf et al (23) have shown that the lifetimes of single SA/biotin bonds for SA attached by its various amines are spread over a wide range and, on average, are about 10 times lower than the lifetime of a single bond between biotin and 1SA anchored by the C terminus of its functional subunit. In the present study, we use the latter, mechanically stronger, attachment geometry to investigate the molecular roots of this discern-ible dependence of mechanical stability on force-loading geometry.…”
Section: Different Unbinding Forces For Different Binding Geometriesmentioning
confidence: 99%
“…This high-throughput nature permits to easily detect conformational heterogeinities 50 or probe the chemical diversity of molecules, such as the effect of small chemical modifications on the side chains of residues directly involved in the protein's mechanical stiffness [51][52][53] , or to probe the effect of small molecules or peptides on the mechanical stability of proteins 54,55 . Magnetic tweezers measurements, by contrast, usually involve the testing of a lower number of molecular entities, although efforts towards parallelization have been successful 24,56 . Unlike in AFM, each of these molecules can be explored for periods that span from minutes to days 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, although some successful examples exist 19,20 , its decreased resolution at low force ranges and instability have prevented the identification of protein folding events and slow-kinetic molecular events that occur at forces below 20 pN and in narrow ranges. By contrast, magnetic tweezers, since its first implementation for protein studies 21 , has demonstrated that its sub-pN resolution and week-long stability in the 0.1-120 pN range outcompete AFM for exploring protein dynamics at low forces and for extended periods [22][23][24][25][26] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, high shear stress unfolds VWF A2 domain to expose the scissile bond Tyr1605-Met1606 for ADAMTS13 cleavage, down-regulating the activity of VWF multimers and preventing excessive platelet aggregation. By the use of single-molecule techniques, we and other groups have demonstrated that A2 unfolding is the prerequisite for ADAMTS13 cleavage ( 92 94 ). Recently, we reported, for the first time, that the interactions between VWF and ADAMTS13 were modulated by mechanical forces, exhibiting multiple bond characteristics: slip bonds, catch bonds, biphasic bonds, and triphasic bonds ( 73 ).…”
Section: The Von Willebrand Factor and Adamts13mentioning
confidence: 98%